FORMULATING STRATEGY OF GREEN OPEN SPACE DEVELOPMENT: A SWOT ANALYSIS - Putri, Irma Apriliana; Sukresna, I Nengah Agus; Pahrudin, Pahrudin; Suhardi, Rizal M. (Elastisitas : Jurnal Ekonomi Pembangunan, 2025)
Green Open Space or Ruang Terbuka Hijau (RTH) is an area or space within the city, which has a function as a park and recreation area, conservation area, and has aesthetic value and has a positive economic impact. RTH will have a significant impact both socially, economically and ecologically if it is developed and managed with the right strategy. The purpose of this research is to formulate a development strategy for one of the green spaces, namely Rinjani Selong Park, East Lombok Regency. The tool for formulating development strategies is using SWOT analysis. Based on the SWOT analysis that describes the internal and external conditions of the Rinjani Park green space, several development strategies can be formulated, including (1) Rinjani Park green space is maintained as a city park which can also be used as a place of recreation and as an appropriate event / cultural performance; (2) improving the quality and quantity of the arrangement of facilities and infrastructure; (3) increasing routine events such as Car Free Day (CFD) and other art performances; (4) increasing multi-stakeholder participation in maintaining and developing RTH; (5) improving the quality and arrangement of vegetation; (6) sustainable environmental conservation efforts; (7) innovative RTH land development such as vertical buildings with the concept of green building. A development strategy that optimizes strengths and opportunities, and anticipates weaknesses and threats will have a positive impact on the social, economic and ecological conditions of the community around Rinjani Park RTH.